1980
DOI: 10.1152/ajpendo.1980.239.1.e75
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation in vivo of PGE receptors and adenylate cyclase stimulation

Abstract: Down-regulation in vivo of liver plasma membrane receptors for prostaglandin E (PGE) was investigated in Sprague-Dawley rats using the 16,16-dimethyl analogue of PGE2, This analogue was used for subcutaneous injections because it escapes the rapid pulmonic degradation characteristic of PGE and was recognized well by liver plasma membrane receptors. Following treatment with the analogue, the concentration of PGE receptors was significantly decreased (-37%, P less than 0.001), but the binding affinity was not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In vivo treatment of rat with PGE2 analogue down-regulates PGE receptor concentration, which is associated with decreased PGE2-stimulated cAMP production, in isolated liver plasma membrane [23] and adipocytes [24]. Since IL-4 and IL-13 suppressed IL-1-induced cyclooxygenase (COX)-2 gene expression, resulting in decreased PGE2 production in murine osteoblastic cells [11,25], the reduction of PGE2 production in IL-4 and IL-13-treated MC3T3-E1 cell may up-regulate PGE2 receptor concentration and PGE2-dependent cAMP response.…”
Section: H Thymidine Incorporation Of Mc3t3-e1 Cells and Cell Prolifmentioning
confidence: 99%
“…In vivo treatment of rat with PGE2 analogue down-regulates PGE receptor concentration, which is associated with decreased PGE2-stimulated cAMP production, in isolated liver plasma membrane [23] and adipocytes [24]. Since IL-4 and IL-13 suppressed IL-1-induced cyclooxygenase (COX)-2 gene expression, resulting in decreased PGE2 production in murine osteoblastic cells [11,25], the reduction of PGE2 production in IL-4 and IL-13-treated MC3T3-E1 cell may up-regulate PGE2 receptor concentration and PGE2-dependent cAMP response.…”
Section: H Thymidine Incorporation Of Mc3t3-e1 Cells and Cell Prolifmentioning
confidence: 99%
“…Our observations suggest an 'end-organ resistance' to the secretory' ef fects of these compounds in the neonatal intestine. The mechanism, at least for PGs, may occur at the receptor level, since PGs rap idly down-regulate PGE receptors in the rat in vivo [23]. Since 5-HT and PGE2 are known to mediate intestinal secretion caused by bacte rial endotoxins [7], a reduced response to these compounds may represent an endoge nous defence against toxin-induced diarrhea at a stage of development when the animal is prone to infection.…”
Section: Response To Secretogoguesmentioning
confidence: 99%
“…There was more total E l (P < 0.004), E l sulfate (P < 0.002) and E 2 (P < 0.096) in uterine flushing of E and PG gilts than C gilts. However, no (Rao, 1973;Dazord et al, 1974;Okamura and Terayama, 1977;Crankshaw et al, 1979;Tepperman and Soper, 1981; Asboth et al, 1985;Hofmann et al, 1985) but linear plots were also reported (Robertson et al, 1980;Robertson and Little, 1983;Asboth et al 1985). Apparent dissociation constants for the highaffinity binding sites in these studies were in nM instead of pM as reported here and in the previous study with pig (Kennedy et al, 1986), indicating a much higher affinity for pig endometrial sites.…”
Section: Uterine Flushingmentioning
confidence: 45%
“…However, PGE 2 has been shown to downregulate its own receptors in rat liver and adipocytes (Robertson et al, 1980;Robertson and Little, 1983) (Lewis and Waterman, 1983) and higher intra-uterine concentrations of PGE 2 were observed in pregnant compared to cycling gilts (Geisert et al, 1982;Keys, 1987). Also, Silastic beads containing E 2 increased the PGE 2 concentrations in the uterine flushing compared to cycling gilts or gilts treated with Silastic beads containing cholesterol (Keys, 1987 (Keys, 1987 (Geisert et al, 1982) inserted into the uterine lumen on day 10 of the cycle increased the high-affinity binding site concentrations and reduced the low-affinity apparent dissociation constants to pregnant and cycling gilts for reasons that still remain unknown.…”
Section: Uterine Flushingmentioning
confidence: 99%